Bahasa Inggris - Libertus Elusandy; Judyanto Sirait; M. Musa Syarif. H (Journal of Teaching and Learning Physics, 2026)
This research aims to create a static fluid assessment that physics teachers can use, utilizing the Evidence-Centered Design approach. Evidence-Centered Design (ECD) is a framework for designing educational assessments that uses a systematic approach to design, develop, and evaluate assessments focused on evidence collection. ECD consists of three main components: claims, evidence, and questions. This research focuses on static fluids as its topic. Research and development (R&D) adapts the ADDIE model (analysis, design, development, implementation, and evaluation) to create the assessment. Analysis is conducted through several stages, namely problem analysis, curriculum analysis, student analysis, and material analysis. The design stage is carried out by determining the assessment objectives, determining the form and number of assessments, designing the assessment components, and writing the assessments. The development stage involves three steps: expert validation, one-to-one trials, and small-scale trials. The results of the research and development of the ECD assessment are deemed feasible based on the results: 1) Validators stated that the instrument falls into the very feasible category with an average Aiken index of 0.87, categorized as very high; 2) one-to-one trial respondents stated that the instrument was very good and the time given was sufficient; and 3) a small-scale trial with a sample of 10 students found that the instrument was very appropriate and the time given was sufficient. Through assessment based on the Evidence-Centered Design (ECD) approach, it is hoped that it can provide guidance to teachers in designing assessments that are appropriate and effective in evaluating each student's understanding